2018
DOI: 10.1590/0034-7167-2017-0452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and management skills for hospital nurses: perspective of nursing university students

Abstract: it was evidenced that college contributed in significant proportions for learning and development of some clinical and management skills in the hospital. Still, despite the identified strategies, managers and training centers need to continuously implement strategies for the development of new skills in nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 12 publications
5
20
0
26
Order By: Relevance
“…Hence, there are some strategies that can be performed by organizations, such as: investment in meetings; permanent education; courses and training. 26 With regard to PHC, one of the challenges to be overcome is related to the workforce. It is highlighted the need for political prioritization of the investment, capable of enforcing the management tools and the expansion of the FHS.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there are some strategies that can be performed by organizations, such as: investment in meetings; permanent education; courses and training. 26 With regard to PHC, one of the challenges to be overcome is related to the workforce. It is highlighted the need for political prioritization of the investment, capable of enforcing the management tools and the expansion of the FHS.…”
Section: Discussionmentioning
confidence: 99%
“…Management of resources—people and material—was highlighted as under‐developed in the curriculum, as well as ‘real‐world’ team working skills. Francis‐Shama's () study of UK students explored a similar area, but in contrast to Leal et al () revealed a disengagement with learning leadership theory within the curriculum. Participants viewed leadership as a personal quality that could not be taught was not a priority skill and could be replaced by ‘more relevant’ topics.…”
Section: Methodsmentioning
confidence: 89%
“…The integration of leadership theory with clinical experience was prominent within two other studies. Leal, Soares, Silva, Bernardes, and Camelo () interviewed students about knowledge and skills development during their undergraduate programme and how this related to working successfully in hospital environments. Focusing on management skills, students cited leadership and decision‐making skills as being vital but felt ill‐prepared to be a leader.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, a comunicação inadequada pode ser uma barreira não somente para a construção de vínculos, mas para uma má qualidade na assistência prestada quando realizada durante a passagem de plantão, por exemplo. A comunicação é uma ferramenta de trabalho que os profissionais de Enfermagem podem utilizar desde a formação, tanto pelos docentes, orientando e estimulando através de metodologias ativas, seja durante os estágios em que os preceptores direcionam os alunos a exercerem a comunicação com o paciente, o familiar, a equipe de Enfermagem e outras equipes dentro da organização de saúde (14) .…”
Section: Discussionunclassified